2004
DOI: 10.1007/s00432-003-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of positron emission tomography on strategy in liver resection for primary and secondary liver tumors

Abstract: Our series demonstrates good sensitivity and specificity for the detection of primary and secondary liver lesions which is superior to ultrasound and CT scan but not to MRI scan. The main value of PET scan consists in the detection of extrahepatic tumor (64%). Due to better detection of extrahepatic tumor, FDG-PET is a very useful addition to the currently used anatomically-based images in all cases of advanced tumor spread with high risk of extrahepatic tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 46 publications
2
49
1
2
Order By: Relevance
“…FDG PET/CT has been known to be less suitable for primary HCC due to limited detectability [17]. However, several studies reported that PET or PET/CT is useful for detection of extrahepatic metastases from HCC [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…FDG PET/CT has been known to be less suitable for primary HCC due to limited detectability [17]. However, several studies reported that PET or PET/CT is useful for detection of extrahepatic metastases from HCC [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the high level of glucose-6-phosphatase in liver tissue leads to the release of FDG-6-phosphate, resulting in reduced accumulation in differentiated HCCs (6). Thus, 18 F-FDG PET has an average false-negative rate of 40%250% for the detection of HCC (7), and data on the role of PET/CT in the detection of HCC metastasis are limited (7)(8)(9). 11 C-labeled acetate PET effectively detects urologic malignancies (10).…”
mentioning
confidence: 99%
“…PET/CT is used mainly to screen for tumor metastasis, and its use is increasing because of an increasing number of candidates for curative treatment such as liver transplantation. Previous studies of PET/CT in patients with primary and metastatic HCC enrolled few patients or were retrospective (7)(8)(9)11,12).…”
mentioning
confidence: 99%
“…18 F-FDG PET/CT is a well-established, noninvasive diagnostic tool for the detection of a variety of malignant tumors such as neck, lung, pancreas, and colon tumors. [5][6][7] However, 18 F-FDG PET/CT is less suitable for the detection of primary HCC because of the variable 18 F-FDG uptake pattern in HCC. [8][9][10] However, 18 F-FDG PET/CT is known to be useful in the evaluation of extrahepatic metastases.…”
mentioning
confidence: 99%
“…[8][9][10] However, 18 F-FDG PET/CT is known to be useful in the evaluation of extrahepatic metastases. 5,9,[11][12][13] Furthermore, pretransplant 18 F-FDG PET/CT has recently been shown to be able to predict a poor outcome after LT for patients with HCC. 14,15 Therefore, 18 F-FDG PET/ CT has been routinely applied to the assessment of patients with HCC before LT at some centers.…”
mentioning
confidence: 99%